DAMPAK, PERSEPSI DAN ADAPTASI BENCANA COVID-19 TERHADAP PERUBAHAN KEGIATAN RELIGI GEREJA KATOLIK DI KEVIKEPAN SURAKARTA - Pranandari, Veronica Damar (Indonesian Journal of Environment and Disaster, 2024)
This research examines the impact, perception, and adaptation of the Catholic Church in the Kevikepan Surakarta to the COVID-19 Disaster, with a focus on the ST Anthony Padua Purbayan Church in urban areas and the St Stephanus Jumapolo Church in rural areas. During the pandemic, religious activities were carried out using an online method, namely live streaming via Youtube as done by the Purbayan Church. Using a qualitative approach method with in-depth interviews and participatory observation, the reaseracher involved the priest, church employees, church administrators and parishioners. The result of the study shows that there is a longing for people in both locations to worship and receive communion directly during the pandemic and restrictions. Health protocols are the main concern of both locations to return to holding offline activities in the new normal period. This study describes the adaptation of the Catholic Church in the Surakarta Diocese to changes due to COVID-19, as well as the perceptions and impact felt by parishioners. The findings are expected to be a reference for understanding changes in religious activities during the pandemic and a reference for further research in geography and sosial disaster studies. Keywords: Adaptation; COVID-19 Impact; Perception; Religious Activities.